Tingkat adopsi teknologi pada usahatani jagung di Kabupaten Konawe Selatan - Assayuthi Mas'uf; Dasmin Sidu; Awaluddin Hamzah; Yusriadin Yusriadin (Universitas Halu Oleo, 2022)
The aim of the study is to analyze the level of technology adoption by farmers in corn farming. This research was carried out in South Konawe Regency, namely Pangan Jaya Village, Lainea District, Sindangkasih Village, West Ranomeeto District and Puwehuko Village, Mowila District in February-March 2021. The population in this study was 451 corn farmers. Determining the number of samples using the Slovin formula, the number of samples was 82 farmers. Determination of the sample using the cluster random sampling method. The variables in this research include: awareness stage, interest stage, assessing stage, trying stage and implementing stage. Data analysis was carried out descriptively. The results showed that the rate of adoption of corn farmers technology in planting activities, pest control and plant diseases as well as in harvesting activities was at the trying stage, while in the activity of using superior seedlings was at the stage of implementing; and in maintenance activities was at the assessing stage. Keywords: adoption; technology; farming and corn.